Biological activity and in vitro spine culture of opuntia dillenii (Ker Gawl.) Haw - Bach Phuong, Vu Thi; Ta Oanh, Tran Thi; Diem Phuong, Quach Ngo (Vietnam Journal of Biotechnology, 2018)
Opuntia dillenii (Ker Gawl.) Haw is used as a traditional medical herb to cure a number of diseases such as boils, burns, gastritis, snake bites ... but so far there have been few studies on biological activities, especially those of spine of cactus. Thus, the bioactive survey of spine and initial study of in vitro culture of cactus is necessary. In this study, ethanol extracts of three parts, pul, brak and spine, were examined with antioxidant activity by Yen and Duh method, and antibacterial activity by determination of zone of inhibition method. After that, these extracts were subjected to preliminary phytochemical testing to detect for the presence of different chemical groups of compounds. Results showed that antibacterial and anti-oxidant activites of spine is higher than those of pulp and bark of Opuntia dillenii. All three parts, pul, bark, and spine, contain phenols, quinones, coumarin, flavanon, isoflavones, isoflavanon, auron, steroids, besides spine contains flavones, chalcon, leucoantocyanidin. In addition, this study also had positive results in experiments on the induction of buds, roots and spines of cactus (Opuntia dillenii). The proliferation of the shoots achieved in MS medium supplemented with 1mg/l benzylaminopurine (BA) and 0,1mg/l naphthaleneacetic acid (NAA). Root formation was influenced by the combination of light and indolebutyric acid (IBA), so the optimal medium is 0,5mg/l IBA set in the absence of light bright. With materials from in vitro micro-propagation process, in vitro spine proliferation experiment was conducted using gibberellic acid (GA3).